PELAKSANAAN UNDANG UNDANG NOMOR 22 TAHUN 1999 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - DJOKO KRISTIANTO, ERNAWATI & (Wacana Hukum, 2008)
Abstract: The Various policy which is gone through  a government representing mirroring of Law No. 22 Year 1999 instructed development of to area can improve the area economics. In order to giving broader autonomy. To finance-related area especially area give by the introductions to be able to fill the source of existing fund as according to potency and each area situation so that later can improve the Original Earnings of Its Area for the sake of its own household defrayal. Keyword : Area Iease, PAD